2009
DOI: 10.1002/app.30656
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(II) amide complexes: Efficient initiators for the living polymerization of methyl methacrylate

Abstract: Lanthanide(II) complexes supported by amido ligands, [(C 6 H 5 [Ln ¼ Sm (3) or Yb (4); THF ¼ tetrahydrofuran], were found to initiate the polymerization of methyl methacrylate (MMA) as efficient single-component initiators (in toluene for 3 and 4 and in toluene with a small amount of THF for 1 and 2) to produce syndiotactic polymers. The catalytic behavior was highly dependent on both the amido ligand and the polymerization temperature. Initiators 3 and 4 initiated MMA polymerization over a wide range of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…1 They have been exhaustively explored as precursors for the preparation of electronic and ceramic materials, 2 as well as catalysts for the synthesis of various valuable chemical products. 3 Moreover they turned out to be efficient initiators for the polymerization of a large range of monomers such as ethylene, 4 styrene, 5 methyl methacrylate 6 or cyclic esters. 7 Formerly, in the pioneering work of Marks it was reported that the strength of the Ln-N bond is comparable to that of the Ln-C bond.…”
Section: Introductionmentioning
confidence: 99%
“…1 They have been exhaustively explored as precursors for the preparation of electronic and ceramic materials, 2 as well as catalysts for the synthesis of various valuable chemical products. 3 Moreover they turned out to be efficient initiators for the polymerization of a large range of monomers such as ethylene, 4 styrene, 5 methyl methacrylate 6 or cyclic esters. 7 Formerly, in the pioneering work of Marks it was reported that the strength of the Ln-N bond is comparable to that of the Ln-C bond.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12][13] Other organolanthanide precursors were reported to similarly favor the syndiotactic enrichment of PMMA, however, not to such a large extent. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] On the other hand, isotactic-enriched PMMA prepared from related group 3 metals are much less common. [31][32][33][34] Regarding rare earth borohydride derivatives, mono-, bis-or tris-borohydridodiamide-diamine, guanidinate, amino-or alkylsubstituted cyclopentadienyl, and alkoxide complexes have been recently reported to polymerize MMA.…”
Section: Introductionmentioning
confidence: 99%